Kompetensi Maturasi dan Fertilisasi Oosit Domba Prapubertas Secara In Vitro (DEVELOPMENTAL COMPETENCE OF MATURATION AND FERTILIZATION PREPUBERTAL SHEEP OOCYTES IN VITRO) - Hafid, Anita; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus (Jurnal Veteriner, 2017)
The objective of this study was to evaluate the maturation and fertilization ability of oocytes frompre-pubertal sheep ovary in vitro. Prepubertal ovary were collected based on the absence of corpus luteum or absence of corpus albicans in both of the ovaries. Oocytes were collected by slicing methode. Only the oocytes which categories of homogeneous cytoplasm and compact cumulus cells were used and it was matured for 24 hours in CO 2 incubator with temperature 39 o C. Oocytes fertilized in vitro used post thawed spermatozoa with concentration 5x10 6 and incubated for 12-14 hours. Oocytes were evaluated on number of oocytes reached MII and number of PN formation. Result of the experiment revealed that there was no significant difference in the percentage of MII oocytes after in vitro maturation (89% vs 90,7%, P>0,05) between prepubertal sheep and pubertal sheep. Meanwhile, the fertilization rate was significantly lower (P>0,05) in prepubertal sheep oocytes compared to pubertal sheep oocytes (60% vs 77,7%). The incidence of polispermic fertilization was higher in prepubertal sheep oocytes than pubertal sheep oocytes (21,8% vs7,4%, P>0,05). In conclusion, prepubertal sheep oocytes and pubertal sheep oocytes have similar in vitromaturation ability, even though the ability to be fertilized of the prepubertal sheep oocytes is lower than the pubertal sheep. ABSTRAK Penelitian ini bertujuan untuk mengetahui kemampuan maturasi dan fertilisasi oosit dari ovarium domba prapubertas secara in vitro. Ovarium domba prapubertas dikoleksi berdasarkan ketidakhadiran korpus luteum atau ketidakhadiran korpus albicans pada kedua ovarium. Oosit dikoleksi dengan metode slicing . Hanya oosit dengan sitoplasma yang homogen dan sel kumulus yang kompak yang dipakai dan dimaturasi selama 24 jam dalam inkubator CO 2 dengan suhu 39 o C. Oosit difertilisasi secara in vitro menggunakan semen beku dengan konsentrasi 5x10 6 spermatozoa/mL dan diinkubasi selama 12-14 jam. Pengamatan dilakukan terhadap kemampuan oosit mencapai tahap metafase II (MII) dan pembentukan pronukleus (PN). Hasil penelitian menunjukkan status inti oosit pada tahap MII tidak berbeda antara oosit domba prapubertas dan oosit domba pubertas (89% vs 90,7%, P>0,05) setelah dimaturasi secara in vitro . Sementara tingkat fertilisasi oosit domba prapubertas lebih rendah (P>0,05) dibandingkan dengan oosit domba pubertas (60,0% vs 77,7%). Kejadian polispermi pada oosit domba prapubertas cenderung lebih tinggi dibandingkan dengan oosit domba pubertas (21,8% vs 7,4%, P>0,05). Dapat disimpulkan bahwa oosit domba prapubertas memiliki kemampuan maturasi yang sama dengan oosit domba pubertas namun memiliki kemampuan fertilisasi yang lebih rendah.
Keywords: fertilization; maturation; oocytes; prepubertal